2022
DOI: 10.1002/ece3.9406
|View full text |Cite
|
Sign up to set email alerts
|

Pleistocene–Holocene vicariance, not Anthropocene landscape change, explains the genetic structure of American black bear (Ursus americanus) populations in the American Southwest and northern Mexico

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 135 publications
0
1
0
Order By: Relevance
“…Our results and previous studies that demonstrated declines in genetic diversity in the Great Basin compared to the Sierra Nevada (Malaney et al., 2018 ) indicates that this population of black bears generally conforms to the center–periphery hypothesis with ecologically marginal habitats on the range edge. Although the large geographic range of American black bears means that several different factors limit their distribution among regions, throughout much of western North America, black bears inhabit high elevation mountains surrounded by desert (Gould et al., 2022 ). Piñon‐juniper also occurs in the fringes of these mountains throughout the southwest, suggesting that similar processes, declining reproduction toward the periphery, limit black bear populations elsewhere and not only the availability of habitat.…”
Section: Discussionmentioning
confidence: 99%
“…Our results and previous studies that demonstrated declines in genetic diversity in the Great Basin compared to the Sierra Nevada (Malaney et al., 2018 ) indicates that this population of black bears generally conforms to the center–periphery hypothesis with ecologically marginal habitats on the range edge. Although the large geographic range of American black bears means that several different factors limit their distribution among regions, throughout much of western North America, black bears inhabit high elevation mountains surrounded by desert (Gould et al., 2022 ). Piñon‐juniper also occurs in the fringes of these mountains throughout the southwest, suggesting that similar processes, declining reproduction toward the periphery, limit black bear populations elsewhere and not only the availability of habitat.…”
Section: Discussionmentioning
confidence: 99%